The status and limits of proper names versus ortography. Remarks on two rules of using the capital letter - Rutkowski, Mariusz (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The paper deals with the problem of the use of capital letters in relation to two selected orthographic rules: the spelling of the names of titles and the names of objects in urban space. It was shown that the current orthographic rules are to a great extent inconsistent and are the result of arbitrary (and, more importantly, incorrect) interpretation of the status of genre names. The postulate of an overriding orthographic rule was formulated, which would require that all words in the structure of proper names be spelled with capital letters. Such a solution would have a systemic value, simplifying the existing chaos and unnecessary detailing of regulations.